Development a Geometric Training Model in Basic Football Techniques - Harmoko Harmoko; Zusyah Porja Daryanto; Ade Rahmat (Jurnal Pendidikan Olah Raga, 2026)
This study aims to produce a geometric-based training model for basic football techniques that is valid, practical, and effective for foster athletes. The research method used is Research and Development (R&D) by adopting the Borg and Gall model development procedures which include the stages of analysis, design, development, implementation, and evaluation. The research subjects involved 30 football athletes in the adolescent age category who were undergoing an intensive technical development program. Data collection instruments used feasibility assessment questionnaires for material experts and basic technique skill test instruments (passing, control, and dribbling) to measure achievements in athletes' motor performance before and after intervention. The data analysis technique applied combined qualitative descriptive analysis and quantitative analysis through t-test (paired sample t-test). Research findings from the sports academic material expert validity team showed a feasibility percentage of 88.50% and from the football coach practitioner expert of 91.20%, both of which fell into the very feasible criteria. The results of the effectiveness test through statistical difference tests showed a significant increase in average scores on passing skill tests from 64.50 to 82.20, control skills from 66.20 to 84.10, and dribbling skills from 61.80 to 80.50. The conclusion of this study is that the integration of geometric concepts designed through the brog and gall structure is proven to be highly valid and effective in optimizing the performance of basic football skills in young athletes.